Pengaruh Stretching Dan Strengthening Core Muscle Terhadap Penurunan Dysmenorrhea Primer - Kemalaningtyas, Rizqiana, Isnaini Herawati S.ST.FT, M. Sc, Arif Pristianto, SSt.FT.,M.Fis (2016)
Dysmenorrhea is a complaint that is often felt during menstruation. Primary dysmenorrhea impact on daily activities. Physical exercise as one of the non-pharmacological therapies to reduce dysmenorrhea due to use of physiological processes that occur in the body. Physical exercise does is stretching and strengthening core muscle. The purpose of this study was to determine the effect of stretching and strengthening core muscle to decrease primary dysmenorrhea. The method used is a quasi-experimental, pre and post test two groups design. The samples in this study were 20 girls were taken by purposive sampling method. Measuring instrument that used in this study is a Visual Analogue Scale (VAS) to measure the intensity of dysmenorrhea. The results of wilcoxon test showed that the intensity of dysmenorrhea in the stretching exercise group declined from 6,2 to 3,7 (p < 0,05) and in the strengthening exercise group declined from 6,8 to 4 (p < 0,05), which indicates that the stretching and strengthening exercises give effect to a decrease in dysmenorrhea. The result of Mann Whitney test is p> 0.05, which showed no difference effect between of stretching and strengthening exercises to decrease dysmenorrhea. However, the result of the difference of mean pre and post exercise showed strengthening exercises greater influence in the decrease of dysmenorrhea than the stretching exercises group (2.80> 2.50).